PANDANGAN DAN SIKAP SISWA MADRASAH ALIYAH TERHADAP NONMUSLIM - Zuriatul Khairi (Lembaga penelitian dan pengabdian kepada masyrakat, 2011)
This research look for Senior High School Student Attitude to non muslem. Research utilizes attitude scale to non muslem by gathers 242 Senior High School Student at Pekanbaru. Finding analysed by quantitave descriptive method. This research finds that Senior High School Student at Pekanbaru gets ekslusif’s view. And attitude to non moslen differenting to terminological its object.